The first results of study of jewel beetles (Coleoptera, Buprestidae) of National Nature Park “Dvorichanskyi” - Терехова, В. В.; Скрильник, Ю. Є. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
In result of analysis of own materials and collections, 28 species of jewel beetles (Coleoptera, Buprestidae) have been identified in the National Nature Park «Dvorichanskyi». 23 species have been registered in the park for the first time. Topical confinement, trophic specialization and biology of identified species have been described. In floodplain meadows rare, locally common species have been registered: Agrilus delphinensis and Agrilus guerini. Among the species associated with chalky steppes, the taxa, which are absent in other habitats in the park (Anthaxia olympica, Sphenoptera cuprina, Meliboeus parvulus ponticus, Agrilus antiquus croaticus) have been revealed. Three species from the studied area (Agrilus guerini, Sphenoptera cuprina, Agrilus antiquus croaticus) have been introduced to the Red Book of Kharkiv Region.